Production of Butanol using Clostridium Acetobutylicum in Anaerobic System - NUR AMIRA SYUHADA BINTI ZAIDI (Multidisciplinary Applied Research and Innovation, 2023)
In batch culture fermentation, butanol was produced using a pure isolation of the solvent-producing Clostridium acetobutylicum. ABE fermentation (acetone-butanol-ethanol) was conducted by using C. Acetobutylicum to produce more butanol. The main objective of this project is to replace the finite sources with renewable resources by undergoing the fermentation process. In order to achieve the main objective, there are three objectives of the research which are to formulate the fermentation medium to produce butanol, to optimize the parameter for fermentation process and the last one is to assess the concentration of butanol and bacteria growth rate. Prior to inoculation, the fermentation media was incubated at 37°C for 24 hours while being sparged with nitrogen gas for 15 minutes. For the results of fermentation products, Gas chromatography or also known as GC was used to analyse the A.B.E fermentation product. In this study, butanol is produced more frequently than ethanol. However, the production of butanol is lower than acetone due to a variety of issues, such as low product yield, insufficient selectivity, and its toxicity, which now restrict butanol synthesis through fermentation. Butanol production peaked at hour 60, when it was at 4.5, before falling to 4.3 during the next 10 hours. For Uv-Vis result of the fermentation media, the absorbance curve of the fermentation media started to drop on day 7. The absorbance started to drop at 450 nm with 2.05 absorbance due to the toxicity of the acetone-butanol-ethanol production in the conical flask.